The mantis shrimp genus Clorida Eydoux & Souleyet, 1842 (Crustacea: Stomatopoda: Squillidae) in Japan, with the first Japanese record of Cloridina ichneumon (Fabricius, 1798) - Nakajima, Hiroki; Ueda, Tetsuya; Itani, Gyo; Osawa, Masayuki (Zootaxa, 2024)
We revised the previous records of Clorida japonica Manning, 1978 and conducted extensive field and museum material surveys in Japan. The material examined included five species of the genus Clorida Eydoux & Souleyet, 1842 as follows: C. japonica; C. albolitura Ahyong & Naiyanetr, 2000; C. denticauda (Chhapgar & Sane, 1967); C. rotundicauda (Miers, 1880); and C. seversi Moosa, 1973. Among them, C. albolitura, C. denticauda, C. rotundicauda, and C. seversi are new to the Japanese stomatopod fauna. Re-examination of the Japanese specimens previously reported as C. japonica has shown that they partially belong to Cloridina ichneumon (Fabricius, 1798), a new record from Japan as well. A key to the Japanese species of Clorida and Cloridina reported in this study is also provided.